2023
DOI: 10.4081/jae.2023.1327
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic tool design improves tillage efficiency, seedbed quality, and straw incorporation during rototilling in conservation farming

Abstract: Rotary tillage facilitates conservation agriculture in rice-based crop farming systems through minimal soil disturbance for seedbed preparation and crop residue management. However, efficiency of rotary tiller blades is hampered by degraded paddy soils and excessive crop residue conditions. Biomimetics presents an edge in the optimisation design of cultivation tools and can be employed to improve the efficiency of rotary tiller blades. This study was designed to evaluate the adaptability and performance of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Through testing, it was found that the average torque of the bionic rotary blade was reduced by 3.14 Nm. Similarly, Torotwa et al [ 29 ] also designed a bionic rotary tiller blade based on the claw toe of a mole rat, as shown in Figure 2 a. Results revealed that the biomimetic blade torque was reduced by 21.05%, the soil was cut into smaller clods, and the straw burial rate and the quality of the seedbed after operation were improved.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through testing, it was found that the average torque of the bionic rotary blade was reduced by 3.14 Nm. Similarly, Torotwa et al [ 29 ] also designed a bionic rotary tiller blade based on the claw toe of a mole rat, as shown in Figure 2 a. Results revealed that the biomimetic blade torque was reduced by 21.05%, the soil was cut into smaller clods, and the straw burial rate and the quality of the seedbed after operation were improved.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
“… Low-resistance soil-engaging components inspired by mole rats. ( a ) Biomimetic tiller blade [ 29 ], ( b ) biomimetic disc [ 30 ], ( c ) biomimetic potato digging shovel [ 32 ], ( d ) biomimetic rotary tillage blades based on five fore claws of mole rat [ 34 ], ( e ) bionic inspired subsoiler [ 35 ]. …”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…et al [41] focused on the design and simulation analysis of blades for producing high-quality seedbeds in paddy field furrows, with a focus on enhancing agricultural productivity through improved soil preparation techniques. Torotwa, I. et al [42] investigated the adaptability and performance of bionic rotary tiller blades utilized in paddy fields, revealing that these biomimetic blades exhibited reduced power requirements while achieving finer and more uniform particle sizes. Pang, C. et al [43] designed a device that can achieve the continuous paving of rice seedling trays without silt blocking or interruption during the process of slurry delivery.…”
Section: Introductionmentioning
confidence: 99%